An Efficient Numerical Algorithm for Solving Fractional Higher-Order Nonlinear Integrodifferential Equations. (2nd November 2015) - Syam, Muhammed I.; Al-Mdallal, Qasem M.; Anwar, M. Naim
Abstract : This paper is devoted to both theoretical and numerical study of boundary value problems for higher-order nonlinear fractional integrodifferential equations. Existence and uniqueness results for the considered problem are provided and proved. The numerical method of solution for the problem is based on a conjugate collocation and spline approach combined with shooting method. Some numerical examples are discussed to demonstrate the efficiency and the accuracy of the proposed algorithm.